Lost opportunities for globalisation, digitalisation, and socially sustainable education? Advocating for digital and global Bildung in Swedish upper secondary schools - Bäcke, Maria; Vigmo, Sylvi (Frontiers in Education, 2024)
In this article, we point to how the making visible of diverse linguistic, digital, and cultural competences can contribute to more sustainable and inclusive classroom contexts and future societies. Western notions of universal knowledge reproduces a western way of viewing the world and, as a result, this usually discounts alternative knowledge systems, which perpetuates inequality and may cause tensions in today’s diverse classrooms. Our 2022 pilot study, drawing on an online survey with more than 700 respondents and focus group interviews with 27 participants, indicates that for some multiethnic, multi-abled, and otherwise diverse upper secondary students underlying, often ethnocentric, norms of Swedish education create hurdles in educational contexts. Firstly, in the Swedish context, non-normative and often global experiences are not recognised at school. Secondly, topics addressed in the courses they take are primarily focused on aspects originating in a Swedish, Nordic, or Western tradition. Curricular policies and classroom practices must take lost opportunities, which we argue are not socially sustainable, into account as a more global and holistic approach when articulating what educational learning is supposed to be about, for, and for whom, and thus integrating learning, digitalisation, and social sustainability.